Risk factors associated with inappropriate empirical antimicrobial treatment in bloodstream infections. A cohort study - Dietl, Beatriz; Boix-Palop, Lucía; Gisbert, Laura; Mateu, Aina; Garreta, Gemma; Xercavins, Mariona; Badía, Cristina; López-Sánchez, María; Pérez, Josefa; Calbo, Esther (Frontiers in Pharmacology, 2023)
Introduction. Bloodstream infections (BSI) are a major cause of mortality all over the world. Inappropriate empirical antimicrobial treatment (i-EAT) impact on mortality has been largely reported. However, information on related factors for the election of i-EAT in the treatment of BSI in adults is lacking. The aim of the study was the identification of risk-factors associated with the use of i-EAT in BSI. Methods. A retrospective, observational study, from a prospective BSI database was conducted in a 400-bed acute-care teaching hospital between January and December 2018. Multivariate analysis using logistic regression was performed. Results. 599 BSI episodes were included, 162 (24%) received i-EAT. Male gender, nosocomial and healthcare-associated acquisition of infection, a high Charlson Comorbidity Index (CCI) score and the isolation of multidrug resistant (MDR) microorganisms were more frequent in the i-EAT group. Adequation to local guidelines’ recommendations on EAT resulted in 91% of appropriate empirical antimicrobial treatment (a-EAT). Patients receiving i-EAT presented higher mortality rates at day 14 and 30 when compared to patients with a-EAT (14% vs 6%, p=0.002 and 22% vs 9%, p<0.001 respectively). In the multivariate analysis, a CCI score ≥3 (OR 1.90 (95% CI 1.16-3.12) p=0.01) and the isolation of a multidrug resistant (MDR) microorganism (OR 3.79 (95% CI 2.28-6.30), p<0.001) were found as independent risk factors for i-EAT. In contrast, female gender (OR 0.59 (95% CI 0.35-0.98), p= 0.04), a correct identification of clinical syndrome prior to antibiotics administration (OR 0.26 (95% CI 0.16-0.44), p <0.001) and adherence to local guidelines (OR 0.22 (95% CI 0.13-0.38), p<0.001) were identified as protective factors against i-EAT. Conclusions. One quarter of BSI episodes received i-EAT. Some of the i-EAT related factors were unmodifiable (male gender, CCI score ≥3 and isolation of a MDR microorganism) but others (incorrect identification of clinical syndrome before starting EAT or the use of local guidelines for EAT) could be addressed to optimize the use of antimicrobials.